GAMBARAN TUGAS DAN TANGGUNG JAWAB BIDAN DESA SELAMA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS CIMAREME - Ratna, Ratna; Susilowati, Virgin (Poltekkes Kemenkes Maluku, 2024)
The COVID-19 pandemic which started at the end of 2019 has had a major impact on various sectors, including the health sector in Indonesia. One group of health workers who are greatly affected are Village Midwives, who play an important role in Maternal and Child Health (KIA) services. During the pandemic, Village Midwives were faced with a double challenge, namely providing MCH services and playing a role in handling COVID-19 at the village level. With social restrictions and changes in health service policies, their duties and responsibilities have become more complex and difficult. This research aims to explore the duties and responsibilities of Village Midwives during the COVID-19 pandemic. This research uses a qualitative research method with a phenomenological approach. The subjects in this research were 5 village midwives who worked in the Cimareme Community Health Center working area. This research was analyzed manually using mixed inductive and deductive data analysis. The results of this research are that during the COVID-19 pandemic, Cimareme Community Health Center Village Midwives received additional duties in handling COVID-19 cases, namely tracing, testing, treatment, recording and reporting. The conclusion of this research is that during the COVID-19 pandemic, the Cimareme Community Health Center Village Midwife faced dual duties and responsibilities, namely carrying out MCH services and handling COVID-19 cases. The researcher's suggestion is that there is a need for further research using mixed methods and increasing the number of informants in order to provide a more comprehensive picture.